Identificación y puesta en valor del parque colinar Pucará Podocarpus, para el fortalecimiento turístico de la ciudad de Loja. - Salinas Merino, Verónica Alexandra (2013)
The city of Loja has a variety of natural and cultural attractions are why from the different viewpoints of the Park can enjoy the enchanting scenery of Loja and surroundings. Part of the old facilities of drinking water tanks supplying the city, located to the south east of the city with an area of 17.9 hectares, surrounded by green areas and paths to moving up to the Mirador Alcazar, and you can see a spectacular view of the city. As entertainment alternatives exist playgrounds and sports fields and restaurant that offers visitors the widest sample lojana gastronomy. Given the problems within the little promotion and dissemination of the park has been raised as thesis topic "Identification and enhancement of Podocarpus PUCARÁ COLINAR PARK, FOR STRENGTHENING OF THE CITY TOURISM LOJA", thus generating new alternatives focused on improving the park to better serve tourists. The overall objective of this paper is to contribute to the development of tourism in the city of Loja through a revaluation of Pucara Colinar Podocarpus Park, to enhance its attractiveness and compliance have been raised three specific objectives: Diagnose the tourist situation Parque Podocarpus Colinar Pucará to know the current situation, develop a proposal for strengthening tourism Colinar Pucará Podocarpus Park through the enhancement of its tourist attractions and finally socialization stakeholders to present the results of the proposal. In this project we have developed all the scientific research process is the same as enforced, to accomplish the first objective was used the same scientific method that allowed me to understand the phenomena that occurred in the study area, synthetic method also allowed order and rebuild broken everything in the analytical method and thus be able to raise the proposal focused on the enhancement of the attractiveness of the park, to see these attractions are carried out to gather information of each one based on the inventory sheet Methodology of Tourist Attractions Tourism Ministry conducting field trips required for direct observation and photographs of each of them. For the second objective descriptive method was used which allowed us to identify the main features that the park has, based on the diagnosis made earlier and gathering information of the attractions. Within the proposal took into account the development of a plan for the promotion and dissemination of the park, with the help of a professional graphic design was drawn sketch of a triptych, totem, fence and information tables, also referred to as tourist signs to the same which is governed by the rules of signage manual Tourism Ministry to set different pictograms, design, size, colors should have these information tools and finally underwent socialization with key stakeholders in the tourist area of the city of Loja thus leaving a record of the work that has been done on the project, meeting the objectives. The recommendations that arise at the end of this work are directed to the Illustrious Municipality of Loja entity that currently manages the park, to take into account the proposal presented in this project to strengthen tourism and Pucara Colinar Park therefore the City of Loja, more of it to provide better care and maintenance services and attractions such as gazebos, sports fields, playgrounds improving their image, another suggestion is to be given monthly training workshops to staff working in the park on customer issues and tourist geography in order to provide better information and assistance to tourists who visit the city. Finally allow conclusions summarize the process that has taken place during the course of this research work and thus disclosed the most significant results obtained: the diagnosis was made in the Park Colinar Pucara was needed to understand their current situation identified that the park is very cozy and popular with the public, but must work on their improvement in infrastructure to offer a better image to tourists, it is clear that the massive turnout by citizens especially late week as entire families come to enjoy the scenery and tranquility that the park offers, a negative part of the park is to insecurity especially in the Mirador Alcázar, this hurts greatly to the development of tourism as it has caused the absence of tourists to this area , which is why we also propose a security plan for the park and finally socializing with stakeholders, was an indispensable contribution to make known the contents of the proposal and thus a record of the work that has been done, considering that one of the main objectives of the National University of Loja is the link with the community.